Using branching Google Forms with multimedia to enhance word problem-solving skills in mathematics - Pillay, Yvette Uzziel (University of the Witwatersrand, Johannesburg, 2024)
South African students perform poorly in mathematics and more specifically in problem- solving. This study found it worthwhile to investigate if branching Google Forms with multimedia was able to enhance Grade 5 students’ word problem-solving skills in mathematics, at a public school in the Johannesburg East region. The chosen theoretical framework was Mayer’s Cognitive Theory of Multimedia Learning. This study employed the action research methodology and compared pre-test and post-test scores after interventions were implemented. Data was analysed using thematic analysis and descriptive statistics. There was an increase in the number of students who indicated having positive emotions towards problem-solving from 22 students in the pre-test to 31 students in the post-test. Students average marks increased from 6 to 11, the class average increased from 40% to 80% and the P value was 0.0001. Overall, out of 41 students, 36 students obtained higher marks in the post-test. All of these statistics indicate that the interventions were successful and that branching Google Forms with multimedia was able to enhance students’ word problem-solving skills in mathematics. Future researchers using Google Forms and conducting research with students from public schools who are not familiar with using the computer, should take more time teaching students how to use the computer as opposed to a computer literacy crash course, which was one of the interventions in this research.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Mathematics; Problem-solving; Word problems; Multimedia; Google Forms; Students; Interventions; SDG-4: Quality education